Virulence of Mycobacterium tuberculosis Clinical Isolates Is Associated With Sputum Pre-treatment Bacterial Load, Lineage, Survival in Macrophages, and Cytokine Response - Tram, TTB; Nhung, HN; Vijay, S; Hai, HT; Thu, DDA; Ha, VTN; Dinh, TD; Ashton, PM; Hanh, NT; Phu, NH; Thwaites, GE; Thuong, NTT (Frontiers Media, 2018)
It is uncertain whether differences in Mycobacterium tuberculosis (Mtb) virulence defined in vitro influence clinical tuberculosis pathogenesis, transmission, and mortality. We primarily used a macrophage lysis model to characterize the virulence of Mtb isolates collected from 153 Vietnamese adults with pulmonary tuberculosis. The virulence phenotypes were then investigated for their relationship with sputum bacterial load, bacterial lineages, bacterial growth, and cytokine responses in macrophages. Over 6 days of infection, 34 isolates (22.2%) showed low virulence (< 5% macrophages lysed), 46 isolates (30.1%) showed high virulence (≥90% lysis of macrophages), and 73 isolates (47.7%) were of intermediate virulence (5-90% macrophages lysed). Highly virulent isolates were associated with an increased bacterial load in patients' sputum before anti-tuberculosis therapy (P = 0.02). Isolate-dependent virulence phenotype was consistent in both THP-1 and human monocyte-derived macrophages. High virulence isolates survived better and replicated in macrophages one hundred fold faster than those with low virulence. Macrophages infected with high virulence isolates produced lower concentrations of TNF-α and IL-6 (P = 0.002 and 0.0005, respectively), but higher concentration of IL-1β (P = 5.1 × 10-5) compared to those infected with low virulence isolates. High virulence was strongly associated with East Asian/Beijing lineage [P = 0.002, Odd ratio (OR) = 4.32, 95% confident intervals (CI) 1.68-11.13]. The association between virulence phenotypes, bacterial growth, and proinflammatory cytokines in macrophages suggest the suppression of certain proinflammatory cytokines (TNF-α and IL-6) but not IL-1β allows better intracellular survival of highly virulent Mtb. This could result in rapid macrophage lysis and higher bacterial load in sputum of patients infected with high virulence isolates, which may contribute to the pathogenesis and success of the Beijing lineage.